Three-Dimensional (3D) Printing as Intellectual Property (UNWE Yearbook, 2021)
The subject matter of this article is the three-dimensional (3D) printing and its protection as industrial property, more particularly as inventions. It indicates the essence of 3D printing and the areas of application of the technology. The protection of the results of 3D printing as inventions is considered, also the advantages and disadvantages of additive manufacturing are analysed. A profile of the enterprises developing 3D printing technologies has been made. The results of the performed patent research are analysed. The filed applications for inventions and the issued patents in the field of 3D printing in a national and international aspect are identified.